ANALISIS STRATEGI PEMASARAN MENGGUNAKAN METODE KOMBINASI SWOT (STRENGTH, WEAKNESS, OPPORTUNITY, THREATS) DAN AHP (ANALYTICAL HIERARCHY PROCESS) - Pradipta, Zein Hilmy Ananda; Suaedi, Daeng Ahmad; Dewa, Weda Adistianaya (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2019)
PT. Karya Graha Primanusa is a company engaged in the field of developers and real estate in the city of Malang. As a developer of residential, ruko, townhouse, which serves investors, businessmen, or professionals who need residential or business areas and offices. Housing developed by PT. Karya Graha Primanusa and one of them that ready is De Sartika townhouse at Batu, which is located in Batu city. The marketing strategy used is still not optimal and minimum target expected sales volume is still not achieved. So do the analysis using method Strength, Weakness, Opportunities, Threats (SWOT) based on internal and external factors on the company. Then combined with Analytical Hierarchy Process (AHP) to determine the best alternative marketing strategy for the company. The purpose of this study is to conduct an analysis to determine marketing strategies used to increase sales volume using a combination of Strength, Weakness, Opportunities, Threats (SWOT) and Analytical Hierarchy Process (AHP) in the PT. Karya Graha Primanusa. Based on the analysis and calculations have been done, it can be concluded that the analysis of marketing strategies with a combination of methods Strength, Weakness, Opportunities, Threats (SWOT) and Analytical Hierarcy Process (AHP) can help the marketing division marketing manager in particular, in increasing the volume of housing sales. This result is evidenced by the results of SWOT analysis, the highest weight value is (Strength-Opportunity) with a value of 4.1624 which can be translated as a strategy to use force to take advantage of existing opportunities. In addition the results of the calculation method of AHP also prove strategic priorities S1 with a value of 3.0855, which perform marketing activities by social media (Facebook, Twitter, & Website).Keyword : Strategi Pemasaran, SWOT, AHP, Analisis